Sejarah Konflik Masyarakat Muslim dan Hubungannya dengan Tingkat Pendidikan di Nagari Saniang Baka dan Nagari Muaro Sumatera Barat - Yummy Jumiati Marsa; Syarbaini Saleh; Suryo Adi Sahfutra (UIN Sumatera Utara Medan, 2021)
This research is a study of the history of border conflicts in Muslim communities and their relationship with the level of education in rural areas of West Sumatra, namely in the Nagari Saniang Baka area with Nagari Muaro, Solok Regency as a case study. The history of the conflict developed along with the education level of the people from the two regions that had a history of conflict. The main focus is the construction of people's thinking about the importance of education before the conflict in 2008 and after the conflict. This study used a qualitative approach with twenty-five key informants, with a process of observation and interviews conducted for approximately six months. The result of this research is that the level of public understanding of education before the conflict between the two villages was very low, this is what makes conflicts easy to occur. Meanwhile, post-conflict, the level of community education is quite good which correlates with the community's understanding that conflict should not occur. Theoretically, conflict is a necessity, it always exists in the course of people's lives, but conflict must be controlled so that it is not destructive. In addition, the level of community education plays an important role in the conflict management process.